Heterologous Omicron-adapted vaccine as a secondary booster promotes neutralizing antibodies against Omicron and its sub-lineages in mice. Issue 1 (31st December 2023) - Liu, Jianyang; He, Qian; Gao, Fan; Bian, Lianlian; Wang, Qian; An, Chaoqiang; Song, Lifang; Zhang, Jialu; Liu, Dong; Song, Ziyang; Li, Lu; Bai, Yu; et al.
ABSTRACT: Over one billion people have received 2–3 dosages of an inactivated COVID-19 vaccine for basic immunization. Whether a booster dose should be delivered to protect against the Omicron variant and its sub-lineages, remains controversial. Here, we tested different vaccine platforms targeting the ancestral or Omicron strain as a secondary booster of the ancestral inactivated vaccine in mice. We found that the Omicron-adapted inactivated viral vaccine promoted a neutralizing antibody response against Omicron in mice. Furthermore, heterologous immunization with COVID-19 vaccines based on different platforms remarkably elevated the levels of cross- neutralizing antibody against Omicron and its sub-lineages. Omicron-adapted vaccines based on heterologous platforms should be prioritized in future vaccination strategies to control COVID-19.